2014
DOI: 10.1111/jbg.12090
|View full text |Cite
|
Sign up to set email alerts
|

BSE‐associated polymorphisms in the prion protein gene: an investigation

Abstract: The aim of this study was to determine the frequency of the 12-bp and 23-bp indel polymorphisms in the prion protein gene (PRNP) in cattle and to investigate the association between these frequencies and the occurrence of bovine spongiform encephalopathy (BSE). There was no significant difference in the 12-bp indel frequency between the BSE animals and control group. For the 23-bp indel, the BSE animals had a significantly lower + + (insins) genotype frequency and + allele frequency compared with the control a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In cattle, insertion/deletion polymorphisms in the regulatory region of the PRNP gene may influence the expression level of PrP C , leading to different incubation periods and an increase in BSE susceptibility 25,26 . According to recent studies, 23-bp insertion/deletion polymorphisms in the promoter region and 12-bp insertion/deletion polymorphisms in the promoter region of intron 1 of the PRNP gene are associated with BSE susceptibility 4,12,27 .…”
Section: Introductionmentioning
confidence: 99%
“…In cattle, insertion/deletion polymorphisms in the regulatory region of the PRNP gene may influence the expression level of PrP C , leading to different incubation periods and an increase in BSE susceptibility 25,26 . According to recent studies, 23-bp insertion/deletion polymorphisms in the promoter region and 12-bp insertion/deletion polymorphisms in the promoter region of intron 1 of the PRNP gene are associated with BSE susceptibility 4,12,27 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the high degree of conservation of the PRPN gene and its ubiquitous expression among mammals suggest several biological roles, such as regulation of the circadian rhythm, central nervous system development, neuronal survival, and maintenance of cellular Ca +2 homeostasis [ 48 ]. In cattle, several studies recently revealed a large allelic variability at the PRPN and PRND loci [ 49 51 ] and also associations with susceptibility to BSE [ 52 54 ]. A recent investigation on the possible association between polymorphisms of the PRPN gene and milk production traits in cattle led to statistically significant results for milk fat content [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a 12-bp indel polymorphism within intron 1 of PRNP has been related to classical BSE (Haase et al, 2007;Gurgul et al, 2012a). However, several studies have failed to find a correlation between 12-bp indel polymorphisms and classical BSE (Hresko et al, 2009;Vernerova et al, 2014). Furthermore, SNP 4136 and 13861 in the noncoding region of PRNP have been shown to confer susceptibility to classical BSE (Murdoch et al, 2010;Jeong et al, 2013).…”
Section: Abstract: Bovine Prion Protein Gene Codon 211 Mutationmentioning
confidence: 99%